2018 Year-End Editorial - Morphett, Taylor (Discourse and Writing/Rédactologie, 2019)
I am thrilled to be writing 2018’s Year-End Editorial for CJSDW/R. One of the (many) benefits to working on an ongoing open access journal is that the editorial occurs after the volume is complete. This allows for a review of the year that considers how the published pieces connect to one another. This year we published a piece from the University of Toronto featuring a trialogue on editing pluriligual scholars’ work at the graduate level between James Corcoran, Antoinette Gagné, and Megan McIntosh. Their conversation argues for “flexible, targeted writing support that challenges narrow epistemologies and stale ideologies regarding taboo editing practices of academic and language literacy brokers involved in the production and revision of thesis writing” (p. 1). This piece really frames the two special sections produced this year in our journal which both take on the question of writing in the university, challenging the conventional practices and arguing for flexible and creative solutions.